2008
DOI: 10.1103/physrevc.77.054317
|View full text |Cite
|
Sign up to set email alerts
|

Strong dineutron correlation inHe8andC18

Abstract: We study the spatial structure of four valence neutrons in the ground state of 8 He and 18 C nuclei using a core+4n model. For this purpose, we employ a density-dependent contact interaction among the valence neutrons, and solve the five-body Hamiltonian in the Hartree-Fock-Bogoliubov (HFB) approximation. We show that two neutrons with the coupled spin of S=0 exhibit a strong dineutron correlation around the surface of these nuclei, whereas the correlation between the two dineutrons is much weaker. Our calcula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 43 publications
1
40
0
Order By: Relevance
“…At the same time, the chemical potential changes its sign at a certain density and finally approaches one-half of the deuteron binding energy at the low-density limit. Recently, a similar situation was also studied for the neutron-neutron (nn) pairs in the 1 S 0 channel [14][15][16][17][18][19][20][21][22][23][24][25]. It was found that in certain (low) density regions the nn pairs can be strongly correlated.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the chemical potential changes its sign at a certain density and finally approaches one-half of the deuteron binding energy at the low-density limit. Recently, a similar situation was also studied for the neutron-neutron (nn) pairs in the 1 S 0 channel [14][15][16][17][18][19][20][21][22][23][24][25]. It was found that in certain (low) density regions the nn pairs can be strongly correlated.…”
Section: Introductionmentioning
confidence: 99%
“…The momentum profile function shown in figure 14 first of all confirms the assignment, as the major part of the 7 He spectrum seems to arise from = 1 neutrons in 8 He. Interestingly enough, at low relative energies a deviation pointing to the appearance of = 0 strength is found with a weight of 4.3(5)% in the 8 He ground-state wave function, which is also expected theoretically [100] with a weight of 7.8 % for the (1s 1/2 ) 2 (0p 3/2 ) 2 configuration. This has been seen before-while analysing the relative energy spectrum of 5 He [71]-in 6 He.…”
Section: The Neutron-rich He Isotopesmentioning
confidence: 66%
“…A direct observation of the final state would be desirable, because the interpretation of the existing data suffers from uncertainties induced by unwanted background contributions that could be avoided with a more selective correlation analysis. Theory predicts that the five-body continuum can be treated with three-body methods [100,101] as strong di-neutron correlations should be present in the system. This is also predicted for the seed nucleus 8 He, so it would be interesting to populate the 7 H system with proton removal from 8 He and compare this to α-removal from 11 Li.…”
Section: 7 H: the Most Extreme Casesmentioning
confidence: 99%
“…nn correlations have been intensively investigated for asymmetric nuclear matter [17][18][19][20][21][22][23][24], and are discussed also in light neutron-rich nuclei such as 8 He [25][26][27][28][29][30] and in medium-heavy neutron-rich nuclei [31,32]. These studies suggest that the nn correlations play an enhanced role at the nuclear surface of finite nuclei and in model studies of infinite neutron matter at low density (weak interactions turned off).…”
Section: Introductionmentioning
confidence: 99%